Comparative Study of the Mechanical Behavior and Corrosion of Alloys Commonly Used in Orthodontic Applications with New Alloy Free Nickel - Moreno, João Roberto Sartori; Pereira, Juliete N; Mariano, Neide Aparecida (Journal of Asian Scientific Research, 2013)
This work is characterized by a comparative study of mechanical properties and corrosion resistance of alloys in common use and under consideration in orthodontics. The study is being conducted in three types of alloys, stainless steel 304V, Ni-Ti alloy which are the most common, and Ni-Free alloy Böhler latest, in order to compare their behavior with mechanical tension stress intraoral and corrosion in environment chloride and artificial salivating of pH 5.99. The corrosion tests were performed prior to ASTM F 2129-08, ASTM B117-07 and beginning all the alloys did not show any sign of general corrosion in chloride solution via Salt Spray, but different strength, especially the alloy Böhler-Free Ni austenite which is presented in value much higher in comparison with the other. However, the electrochemical behavior by test EPR-DL (Electrochemical Potentiodynamic Reactivation - Double Loop) has still been somewhat similar, with the pitting critical potential indefinite absence of hysteresis during the scan potential in descending order, showing an absence of marked growth of density current. Also, the estimate of the forces involved during orthodontic correction, phase alignment and leveling, it was a finite element simulation of the activation of the teeth that showed lower levels of stress for the alloy NiTi than for stainless steel 304 V and Free-Ni alloy.